Drainage evolution in the Polish Sudeten Foreland in the context of European fluvial archives. Issue 2 (7th December 2018) - Krzyszkowski, Dariusz; Bridgland, David R.; Allen, Peter; Westaway, Rob; Wachecka-Kotkowska, Lucyna; Czerwonka, Jerzy A.
Abstract: Detailed study of subsurface deposits in the Polish Sudeten Foreland, particularly with reference to provenance data, has revealed that an extensive preglacial drainage system developed there in the Pliocene–Early Pleistocene, with both similarities and differences in comparison with the present-day Odra (Oder) system. This foreland is at the northern edge of an intensely deformed upland, metamorphosed during the Variscan orogeny, with faulted horsts and grabens reactivated in the Late Cenozoic. The main arm of preglacial drainage of this area, at least until the early Middle Pleistocene, was the Palaeo–Nysa Kłodzka, precursor of the Odra left-bank tributary of that name. Significant preglacial evolution of this drainage system can be demonstrated, including incision into the landscape, prior to its disruption by glaciation in the Elsterian (Sanian) and again in the early Saalian (Odranian), which resulted in burial of the preglacial fluvial archives by glacial and fluvioglacial deposits. No later ice sheets reached the area, in which the modern drainage pattern became established, the rivers incising afresh into the landscape and forming post-Saalian terrace systems. Issues of compatibility of this record with the progressive uplift implicit in the formation of conventional terrace systems are examined, with particular reference to crustal properties, which are shown to have had an important influence on landscape and drainage evolution in the region.